Surprise me [compact disc, unabridged] : a novel - Kinsella, Sophie (Random House Audio, 2018)
After being together for ten years, Sylvie and Dan have all the trimmings of a happy life and marriage; they have a comfortable home, fulfilling jobs, beautiful twin girls, and communicate so seamlessly, they finish each other's sentences. However, a trip to the doctor projects they will live another 68 years together and panic sets in. They never expected 'until death do us part' to mean seven decades.